Update on Fe-dependent oxidative metabolism in vivo: an integrative view - Piloni, Natacha Estefanía (2016)
Fe is essential for human life because it constitutes the required cofactor for proteins of diverse biological functions. However, the development of oxidative stress by exposure to excessive Fe, share signaling pathways with other treatments including activation of redox-sensitive factors. This study was focused on the comparison on the effects of Fe in the brain and other organs in vivo. The oxidative effects triggered by Fe overload strongly depend not only on the administration protocol, but also on the Fe-compound used, and the studied organ. In both the liver and the brain, Fe content drastically increased after Fe-dextran administration. However, the comparatively lowlipid peroxidation in the brain as compared to the liver, suggested that Fe-dependent oxidative stress might involve mechanisms of different nature. In the brain, acute and subchronic administration of Fe-dextran triggered signaling processes that lead to the prevention of injury by the participation of catalase activity as an antioxidant protection.This brief summary opens a huge range of possible points of risk, as well as opportunities, to encounter situations in which the appropriate election of the Fe management protocol could be able of allow oxidative stress to exert beneficial effects.